NILAI-NILAI LOKAL MASYARAKAT PESISIR DALAM UPAYA PELESTARIAN SUMBERDAYA PESISIR DI KOTA BENGKULU - Heni Nopianti; Sri Handayani Hanum; Sumarto Widiono (Jurnal Sosiologi Nusantara, 2015)
This study aims to identify and describe the local values of the coastal community of Bengkulu city in managing coastal resources. The data and information were collected from a number of informants who were selected based on purposive sampling technique. The required data were collected through interviews, observation, and documentation. Data analysis was done simultaneously in conjunction with the data collection process by using conventional analytical techniques applicable in qualitative research. The result of this study shows that there are a number of local values in the coastal community of Bengkulu city, either they are still alive or have been ignored. The values had been continuously maintained for the preservation of coastal resources are: using boats (canoes) and traditional equipments in fishing instead of using trawls; avoid using explosives and poison potassium in making the catch; making restrictions on the catchment area; managing household waste; doing reforestation; and not catching the sharks.Keywords : Local Value, Management, Coastal Resource